Validation of an instrument for patient classification to support obstetric nursing care - Vanessa Damasceno Laporte; Clara Fróes de Oliveira Sanfelice; Ariane Polidoro Dini (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to develop and validate an instrument for the classification of pregnant and postpartum women according to the demand for nursing care. Methods: a methodological study conducted in three stages: 1) construction of the instrument based on literature review; 2) content validation using the Delphi technique with 12 experts; and 3) Evaluation of the convergent construct validity through the correlation between the scores of the constructed instrument and the Fugulin instrument. Results: an instrument with ten indicators of specific care for pregnant and postpartum women was developed. A content validity index higher than 0.9 was obtained, requiring only one round of the Delphi technique. The Spearman coefficient was 0.64 between the instruments, indicating a strong correlation. Conclusions: the classification instrument specifically constructed for pregnant and postpartum women showed evidence of content validity and convergent construct validity with a widely used instrument in the national territory.